Manipulation of Mg2+-Ca2+ Switch on the Development of Bone Mimetic Hydroxyapatite - Andrés, Nancy Carolina (2017)
Ionic substitution can affect essential physicochemical properties leading to a specific biological behavior upon implantation. Therefore, it has been proposed as a tool to increase the biological efficiency of calcium phosphate based materials. In the following study, we have evaluated the contribution of an important cation in nature, Mg2+, into the structure of previously studied biocompatible and biodegradable hydroxyapatite (HA) nanorods and its subsequent effect on its chemical, morphology, and bone mimetic articulation. Mg2+-substituted HA samples were synthesized by an aqueous wet-chemical precipitation method, followed by an hydrothermal treatment involving a Mg2+ precursor that partially replace Ca2+ ions into HA crystal lattice; Mg2+ concentrations were modulated to obtain a nominal composition similar to that exists in calcified tissues. Hydrothermally synthesized Mg2+-substituted HA nanoparticles were characterized by X-ray powder diffraction, FT-NIR and EDX spectroscopies, field emission scanning and high resolution transmission electron microscopies (FE-SEM, H-TEM). Molecular modeling combining ab initio methods and power diffraction data were also performed. Results showed that Mg2+-substitution promoted the formation of calcium deficient HA (cdHA) where Mg2+ replacement is energetically favored at Ca(1) position in a limited and specific amount directing the additional Mg2+ toward the surface of the crystal. The control of Mg2+ incorporation into HA nanorods gave rise to a tailored crystallinity degree, cell parameters, morphology, surface hydration, solubility, and degradation properties in a dose-replacement dependent manner. The obtained materials show qualities that conjugated together to drive an optimal in vitro cellular viability, spreading, and proliferation confirming their biocompatibility. In addition, an improved adhesion of osteoblast was evidenced after Mg2+-Ca2+ substitution.